2007
DOI: 10.1017/s1138741600006570
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Improvement Writing Program According to Students' Reflexivity Levels

Abstract: After designing a writing program to enhance students' reflexivity and thus improve their compositions (García & de Caso, 2002a, 2002b, the aim of the research project was to show how reflexivity levels could influence the effectiveness of this program. This writing instruction through reflexivity was carried out with 5th and 6th grade students with learning disabilities (LD) and/or low achievement (LA) during 25 sessions. One hundred participants were assigned to either the experimental group (n = 49), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
2
0
6
Order By: Relevance
“…Firstly, the teachers carried out an initial screen which comprised an interview or questionnaire about the achievement of students with greater difficulties in writing tasks, and this opinion was confirmed by a writing achievement task. For this, every student had to accomplish a part of the EPP y FPE (Planning Processes and other Writing Psychological Factors Assessment), to assess writing proficiency -to establish that every student had a delay of at least two years in composition writing; this assessment has been used in preview studies (García & de Caso, 2007). The results confirmed that the tasks fulfill the desired psychometric properties with a high reliability (α 968 = .88) for internal consistency; the validity of construct, structural and of content is adequate and so, we can state that the device meets with the desired psychometric properties (Fidalgo, 2005).…”
Section: Participantsmentioning
confidence: 99%
“…Firstly, the teachers carried out an initial screen which comprised an interview or questionnaire about the achievement of students with greater difficulties in writing tasks, and this opinion was confirmed by a writing achievement task. For this, every student had to accomplish a part of the EPP y FPE (Planning Processes and other Writing Psychological Factors Assessment), to assess writing proficiency -to establish that every student had a delay of at least two years in composition writing; this assessment has been used in preview studies (García & de Caso, 2007). The results confirmed that the tasks fulfill the desired psychometric properties with a high reliability (α 968 = .88) for internal consistency; the validity of construct, structural and of content is adequate and so, we can state that the device meets with the desired psychometric properties (Fidalgo, 2005).…”
Section: Participantsmentioning
confidence: 99%
“…Incremento observado en las medidas sobre motivación examinadas (atribuciones del fracaso al esfuerzo, atribuciones de éxito al esfuerzo), confirmándose de este modo la segunda hipótesis. Evidencia que encaja con los resultados obtenidos en investigaciones e intervenciones anteriores (García, de Caso, Fidalgo, Arias-Gundín, y Torrance, 2010;García y de Caso, 2006a;García y de Caso, 2006b;García y de Caso, 2007;Nguyen y Abbott, 2016;Shahrokhi, 2017). En este sentido, García y de Caso (2006a) y Shahrokhi (2017) observaron que tras la implementación del programa instruccional los niveles de motivación de los estudiantes se incrementaron.…”
Section: Discussionunclassified
“…En general, las investigaciones realizadas en torno a estos dos enfoques se han llevado a cabo de manera presencial y se han centrado fundamentalmente en el análisis de la escritura académica (Reguera, 2014), desarrollándose la mayor parte dentro de la educación formal obligatoria, principalmente Educación Primaria (Álvarez y García, 2014a, García y de Caso, 2006aGarcía y de Caso, 2006b;García y de Caso, 2007;Iandolo et al, 2013;Robledo y García, 2013) y Secundaria (Álvarez y García, 2014a; Arias-Gundín y y la no obligatoria, especialmente la universitaria (Camps y Castelló, 2013;Hasan y Akhand, 2010;Reguera, 2014), obviándose de este modo, a la población adulta que se encuentra fuera del sistema educativo y académico, y las posibilidades que ofrece la instrucción virtual (Álvarez y García, 2014a; Arias-Gundín y Hasan y Akhand, 2010;Reguera, 2014).…”
Section: Delimitación Del Problema Objetivo E Hipótesis De Investigaunclassified
“…Tras los resultados de la implementación de un programa, formulado inicialmente con el objetivo de incrementar los niveles de reflexividad en los niños (García y De Caso, 2002ay 2002b, se exploró el impacto de los niveles de reflexividad sobre la eficacia del programa (García y Caso-Fuertes, 2007).…”
Section: La Dimensión Reflexividad-impulsividadunclassified